PEMBERDAYAAN USAHA KECIL MENENGAH MELALUI PELATIHAN TATA KELOLA PEMBUKUAN DAN PENINGKATAN PRODUKSI PEMASARAN DENGAN TEKNOLOGI PADA USAHA SOUVENIR DI GORONTALO - Andi Yusuf Katili; Mohammad Imran; Agus Pariono (Universitas Bina Taruna Gorontalo, 2022)
In its second term, the Jokowi government paid great attention to improving small and medium enterprises (UKM). SMEs are a business sector that plays an important role in the Indonesian economy, both in terms of contribution to National GDP and in terms of employment. SMEs are required to make improvements and changes in order to increase their competitiveness. At the end of 2019 until now, all countries in the world were shocked by the emergence of the corona virus or Covid-19. The current Covid-19 pandemic inevitably has an impact on various sectors. One type of UKM in Gorontalo that still exists and plays a very important role in promoting typical Gorontalo musical instruments (Polo Palo) and carrying out simple processing of waste (used goods), handicraft piggy banks; calligraphy frames and wall clocks made from used goods, in the form of souvenirs or handicrafts and absorbing local workers who are creative and innovative regarding traditional art ideas and concepts.